This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.View Full Document
Unformatted text preview: r = 5/2 (5/2, -5/2) 35. Multiply the second equation by -1 3x + z + 2w +18v = 0-4x + y - w - 24v = 0 7x y + z + 3w + 42v = 0 4x + z + 2w + 24v = 0 37. Replace the second equation by the sum of itself and -2 times the first equation x + y + 2z + 3w = 1 -y - 1z - 2w = -1 3x + y + 4z + 5w = 2 2x + y + 3z + 4w = 1 x + y + 2z + 3w = 1-2x 2y - 4z -6w = -2-y - 1z 2w = -1...
View Full Document
- Spring '09